The Impact of Education on Knowledge and Use of Contraceptive Methods: A Comparative Analysis of Educated and Under educated Populations - Suhail, Zarish; Hussain, Mudassar; Hasan, Sajjad Ul; Huda, Amtul; Raza, Tahira; Javaid, Aqsa (Pakistan Journal of Health Sciences, 2025)
Abstract: Contraception is a critical aspect of public health, significantly influenced by education, which enhances individuals’ knowledge and decision-making regarding contraceptive methods. Objectives: This study aims to assess the impact of education on the knowledge and use of contraceptive methods by comparing educated and undereducated populations. Material and Methods: A cross-sectional study was conducted among 400 participants in Lahore, using convenience sampling. Data were analyzed using SPSS version 23, with frequency, percentages, mean, and standard deviation applied. Results: The results show that higher education levels are associated with significantly greater knowledge of contraceptive methods, with 35.2% of college/university-educated participants being aware of condoms, compared to only 15.2% of uneducated participants. Moreover, the use of modern contraceptive methods, such as condoms and oral contraceptives, was notably higher among the educated group (18.8% and 28.7%, respectively) than among the uneducated group. Discussion: The study also highlights significant disparities in contraceptive use and knowledge between educated and undereducated populations, emphasizing the socio-economic and cultural barriers faced by the latter. Conclusion: In conclusion, the findings reinforce the critical role of education in enhancing contraceptive knowledge and use, highlighting the need for targeted public health interventions to address the unmet contraceptive needs of undereducated populations.